The Effect of Several Acids dan Natural Acid Concentration on the Phycal, Chemical, and Organoleptic Quality of Goldfish Naniura - Bethany Bethany; Elisa Julianti; Mimi Nurminah (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The aim of this research was to find the effect of the natural acids and acid concentration in producing naniura with the best quality. This research was using completely randomized design with two factors, i. e several natural acid (A): (rough lime, kaffir lime, lime, calamondin) and acid concentration (K): (20%, 30%, 40%, 50%). The results showed that the interaction between several natural acid dan acid concentration had a highly significant effect (P<0,01) on acid degree (pH) and total acid and had a significant effect (P<0,05) on proteins content. The increasing concentration of natuural acid increased tatal acid, decreased pH and decreased chemical characteristics (total volatile bases nitrogen, water content, proteins content), and also influenced hedonic index flavour of goldfish naniura. Goldfish naniura with the best quality based on chemical and organoleptic characteristics by organoleptic test with hedonic index flavour was the calamondine with concentration of 40%. Keywords : Goldfish Naniura, Rough Lime, Kaffir Lime, Lime, Calamondin